CONTROLLING OF IMPORTED OR EXPORTED GOODS RELATED TO BRAND PROTECTION BY CUSTOMS - MUCHTAR ANSHARY HAMID LABETUBUN; MARSELO VALENTINO GEOVANI PARIELA (UNTAG Law Review, 2020)
Customs regulations in Indonesia, there is also a legal mechanism to protect brands. Provisions in Chapter X of Law, Number 10 of 1995 concerning Customs as amended by Act Number 17 of 2006 concerning Amendments to Law Number 10 of 1995 concerning Customs, includes a prohibition on import or export restrictions and controls on the import and export of goods the results of infringement of Intellectual Property Rights including Trademark Rights. The role of Customs in the framework of protecting registered brands is as a traffic surveillance apparatus for goods entering or leaving Indonesian territory, the Directorate General of Customs and Excise (DJBC) is required to control the import-export of products resulting from violations in the field of trademark rights, and intellectual property rights and by court order can stop the entry and exit of goods infringing trademark rights. The implementation of the trips agreement in the laws and regulations on Indonesian customs can contribute to the protection of registered trademarks, especially in terms of being the front door in overcoming violations of trademark rights in Indonesia.